Language Plurality as Cultural Characteristics of Southeast Asia: A Review of John F. Hartman’s Thesis - Agus Suwignyo (Diponegoro University, 2022)
John F. Hartmann (1986) argued that the spread of the Indic languages in Southeast Asia took place in different overlapping periods, through which the region underwent a process of indinization. Hartmann’s thesis is very important to help understand the making of cultural networks in Southeast Asia. However, the scope of his thesis was limited by its sole focus on the Indic languages, on the mainland Southeast Asia, and on the early historic period of the region. Taking Hartmann’s thesis as a starting point, the present paper examined the spread of languages in Southeast Asia as a cultural network. By using a comparative bibliography method and by analyzing existing studies on the pre-historic and the historic stages of language development in Southeast Asia, this paper argues that the indinization as suggested by Hartmann comprised only the first phase in the overall making of the language-based cultural network in Southeast Asia. Bibliographical sources show that the language-based cultural network in Southeast Asia involved at least three other periods in addition to indinization, that is chinaization, arabization, and europeanization. In Southeast Asia, the spread of the cultural network depended not so much on a lingua franca – a language of unity – as on the plurality of languages. The successive phases in the spread of different civilizations created a Southeast Asian plural society, in which various linguistic branches molded as one of the most remarkable cultural notions of the region. Hence, the idea to have one regional language of integration, for example in the current context of ASEAN, contradicted against the cultural history of Southeast Asia. It is because Southeast Asia has become integrated through a pluralization, not unification, of languages.